Improvement of salivary flow and oral wetness by a lip trainer device and sonic toothbrush in older Japanese men and women with dry mouth - Uchida, Keiichi; Saleem, Murtaza; Ozaki, Yuki; Taguchi, Akira; Iwai, Yukiko; Yoshinari, Nobuo; Masuda, Yuji; Nakamura, Suguru; Sumi, Yasunori (Journal of Oral Science, 2019)
Dry mouth, caused by decreased salivary gland function and/or weak salivary stimulation, can severely affect oral health in older individuals. Therefore, the aim of this study is to evaluate whether a lip trainer device and sonic toothbrush can improve salivary flow and oral wetness in older patients complaining of dry mouth. Overall, 39 subjects aged ≥60 years who had at least 20 natural teeth were randomly assigned to use a lip trainer device (group P, n = 13) or a sonic toothbrush (group S, n = 13). The subjects who did not experience oral dryness were included as controls (group C; n = 13). The unstimulated and stimulated salivary flow rates and oral wetness were measured at baseline, 1 and 6 months. The unstimulated salivary flow significantly increased in both groups at 1 and 6 months (P < 0.05). The stimulated salivary flow was also significantly increased in group P (P < 0.01) compared with the level at baseline. However, no significant difference was observed over time in group S. Oral wetness of the tongue and buccal mucosa in group P had significantly improved at 1 and 6 months (P < 0.05). Dry mouth in older individuals may be improved by using a lip trainer device or a sonic toothbrush.